Synthesis and Characterization of SCDs/TiO2 Composite - Aritonang, Anthoni Batahan; Sapar, Ajuk; Sari, Heni Puspita; Ardiningsih, Puji; Adhitiyawarman, Adhitiyawarman (CHEESA: Chemical Engineering Research Articles, 2022)
Synthesis of sulphur-doped carbon nanodots immobilized on the TiO2 surface (SCDs/TiO2) composite was carried out using the sol-gel method with SCDs and titanium tetraisopropoxide (TTIP) as precursors. SCDs were prepared from citric acid monohydrate, urea, and sodium disulphite using the microwave technique. SCDs/TiO2 was then visually observed under UV 365 nm and characterized by UV-Vis diffuse reflectance spectrophotometry (UV-Vis/DRS), Photoluminescence (PL) spectroscopy, Fourier transform infrared (FT-IR), and X-ray diffraction (XRD). The SCDs/TiO2 composite product had a brown solid with a green luminescent under UV light. Furthermore, UV-Vis/DRS for variations in SCDs concentrations of 0.5%; 1.25%, and 2.5% showed Eg values of 2.33 eV, 2.14 eV, and 1.61 eV, respectively. The results showed that SCDs caused the maximum emission peak (λEm) to redshift and also affected the intensity of PL TiO2. There was also a shift in the absorption peak towards the visible light region. Based on the results, the 0.5% SCDs/TiO2 was the optimum concentration with the lowest intensity as an indication of separation of the (e-) and (h+) charge pairs, which greatly enhanced the photocatalytic efficiency.